PENGARUH PENGGUNAAN MODEL INSIDE OUTSIDE CIRCLE TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS X SMA NEGERI 1 KECAMATAN LAREH SAGO HALABA - Wirda Linda; Indah Rahmalia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to describe the effect of using the Inside Outside Circle Model (Small Circle-Large Circle) on Students' Poetry Writing Skills. This type of research is quantitative research with experimental methods. The population in this study amounted to 257 students and a sample of 55 students which was divided into two classes, the experimental class and the control class. The sampling method is using purposive sampling. The instrument in this study used a performance test with aspects of theme, diction, imagery and figurative language assessment. Data analysis shows that the Inside Outside Circle (small circle-big circle) model has an effect on learning to write poetry in Indonesian language subjects in the experimental class. This is evidenced by an increase in student scores, which at the time of the pre-test the mean (X ) was 72.56. After applying the Inside Outside Circle learning model (small circle-big circle) in the learning process at the post-test time, the average value (X ) was 87.4. This can be seen from the results of the comparison of tcount with ttable (4.73 > 2.021), because tcount is greater than ttable then Ha (alternative hypothesis) is accepted. So, it can be concluded that the learning outcomes of the experimental class students who were taught by the Inside Outside Circle learning model (small circle-big circle) were better than the learning outcomes of the control class students who were taught using conventional methods.